Pollen analysis and 14C dating in outlining vegetation history of the primeval forest Fiby urskog, south Sweden - Skoglund, Jerry; Hytteborn, Håkan; Karlsson, Sven (Swedish University of Agricultural Sciences, 2019)
The data file is the raw data collected in Fiby urskog, south Sweden in order to perform a paleoecological study, covering ca 7000 years, using pollen analysis, including spores, charcoal fragments and mineral particles from a small wetland basin. 14C dating, diatom analysis and shore displacement data aided in dating the vegetation succession. Indicators of human impact and other disturbances, during the last ca 1000 years, are given particular attention as well as Picea immigration.

Pollen was extracted from the sediment with a Russian peat corer (diameter 5 cm) every 2.5 cm down to ca 100 cm. Standard acetolysis method was used to extract pollen and spores. Treatment with hydrofluoric acid was performed on the lowermost part of the sediment to separate the large number of mineral particles.

Materialet avser rådata som legat till grund för en pollenstudie vars syfte är att beskriva vegetationshistorien i Fiby urskog, Uppland, de senaste ca 7000 åren. En ca 100 cm sedimentpropp togs i en central våtmark. Tonvikt ligger på de senaste ca 1000 åren där granens invandring och eventuell kulturpåverkan betonas särskilt. 14C-analys har använts vid åldersbestämning liksom landhöjningsdata, diatomanalys och stratigrafi.

Se engelska katalogsidan för mer information: https://snd.gu.se/en/catalogue/study/SND1124
Pollen analysis and 14C dating in outlining vegetation history of the primeval forest Fiby urskog, south Sweden
Keywords: primary forest; primärskog; paleoecology; pollen analysis; terrestrial; Habitats and biotopes; Naturtyper och biotoper; palynology; palynology; mire; myr; picea abies; picea abies; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biological Sciences; Biologi; Biota; Biologi och ekologi; Geoscientific Information; Geovetenskap